Proposta metodológica de avaliação de riscos em barragens do nordeste brasileiro - estudo de caso: barragens do estado do Ceará - Fontenelle, Alexandre de Sousa (2007)
The methodological proposal of risk analysis in dams of the brazilian northeast, with case study of 77 dams (62 State and 15 Federal dams) in the State of Ceará, aims to hierarchize a set of dams from the inspections, incorporating level of danger, probabilities, costs, severity (damage to be avoided), equivalent net benefits, which is the cost of elimination of the anomalies with level of danger reduced from the severity and its risks to search for the efficiency in the application of the financial resources improvement of dams safety to the welfare of the society. The proposal begins with the determination of the annual rupture probability (from the hazard) and the costs (from the rehabilitation of an hypothetical rupture of the dam and from the elimination of the anomalies that presents hazard). Three criteria were considered for classification of dams, named as Criteria 1, 2 and 3, as follows: Criterion 1: best efficiency in application of the resources for the physical reduction of hazard of the dams (NPB/CeNP); Criterion 2: economic equivalent Net Benefit (BLe); and Criterion 3: Score of Risk (ER) developed from three known risk qualitative methodologies. The proposal methodology permits the decision makers to classify the dams from the weigh of the three criteria set before. The methodology also permits to verify which of the three criteria presents better efficiency in application of the financial resources to reduce the risks, and also enable to perform an economic efficiency analysis having as base the economic equivalent net benefit in function of the value invested in the elimination of the danger. The methodology proposes to obtain the economic risk from the theory of Fuzzy Sets using the two main uncertainties of the model: the estimation of the probability of annual rupture and the cost of rehabilitation of the dam, applying in the two criteria that consider costs (criteria 1 and 2). In the case study it was observed in the criterion 2 that the risk increases with investments. In the case of partial use of resources, the risks are lesser for the criterion 2 (BLe). In this criterion the economic risk increases with the spent resources. The same does not happen in criterion 1, which presents an intermediate minimum risk. The diffuse economic risk of the equivalent net benefit to be negative is 3,83%, to both criteria, in case of eliminating all the hazards.